ESTABLISHING COMPETITIVE ADVANTAGE TO IMPROVE BUSINES PERFORMANCE - Abdurrahman, Abdurrahman (Fakultas Ekonomi dan Bisnis, Universitas Teknologi Sumbawa, 2018)
The purpose of this research is to analyze the influence of market orientation and innovation on competitive advantage and business performance at restaurant in Mataram City. The problem in this research is ?How establishing competitive advantage to improve business performance?. Results of interview with respondents, it describes the problems faced by owner culinary business, including the decline in their business performance, lack of innovation, lack of professional labor, and the competitive challenge faced by owner of culinary business. The population of this research is the restaurants in the year period of 2011-2015 wich are registered in The Department Culture and Tourism of Mataram City. The samples of this research are restaurant in Mataram City of West Nusa Tenggara with total sample is 120 respondents. The data in this research was taken using questionnaire and interview. Then, the data was analyzed using Structural Equation Modeling (SEM-Amos). All of the hypothesis in this research are accepted as shown by Critical Ratio (CR) ? ± 1.96 and Probability (P) < 0.05. The analysis showed that the direct effect of innovation on business performance is higher than the effect of market orientation on business performance (0,458 compared to 0,223). Indirect effect of innovation on business performance through strategic competitive advantage is higher than the effect of market orientation on business performance through competitive advantage (0,130 compared to 0,096)